Curriculum Transformation: From Didactic to Competency-Based Programs in Pharmaceutical Medicine - Chisholm, Orin (Frontiers in Pharmacology, 2019)
As the complexity of the pharmaceutical industry increases and with the current disruptive forces affecting it, there is an increasing need for suitably-qualified personnel. Universities must respond to the need for graduates with the appropriate skills and knowledge to enable the transformation and future growth of this industry. Restructuring educational offerings to focus on graduate attributes, such as analytical and critical thinking, collaboration and problem solving, creativity, flexibility and self-direction in the context of the pharmaceutical industry facilitates the changes needed for future growth and viability. This paper discusses the process of program transformation to enable the development of graduates who can respond to these challenges in the pharmaceutical industry.